PENGELOLAAN TWITTER DEBAGAI MEDIA KOMUNIKASI PADA KOMUNITAS FANDOM ID YOGYAKARTA - Linda Ramadhan Maya Sekar Wangi, Buddy Riyanto (Solidaritas, 2018)
ABSTRACT The community is on one of these social media Fandom ID formed in april 2015, consists of the internet users who often keep a journal (blogging) about football that can be received and read by followers Fandom id. The main goal of peneltian to describe the management of twitter as a communication media on the community of fandom. Study of the theory used is a social media management consists of planning, activation, and surveillance as well as optimization.Methods a descriptive qualitative approach uses, the type of data used the data of the secondary data and prime. The technique of determination of the informants using purposive sampling, data collection is done with the interview and documentation. As for the data analysis technique used to use descriptive qualitative analysis.Based on the results of the analysis of the obtained conclusions that the management of Twitter as a communication medoa basically covers three things, namely planning, activation and monitoring, and optimization. The planning undertaken fandom hold meetings and evaluation every day and make a strategy of what to do to enable the target readership (traffic). Activation and subsequent supervision of fandom can accept Disclaimer and remove a twitt judged unsuitable, fandom had already ruled the football field could therefore filter which should be shared and which ones are unnecessary. Additional activation and supervision after the last optimization. optmalisasi covers all processes where Besides doing a meeting and evaluation of the fandom do editing that can be viewed from google trend of what is being discussed and many become trending on twitter at that moment. In conclusion the management of twitter as a communication medium in fandom id quite effective because its spread through twitter a very real time and easy to read at any time by the followers (follower) of fandom. Management via the medium of twitter can also invite the follower to keep active and participate to discuss what is currently crowded discussed. In addition this fandom is always accountable management of content produced by displaying the name of the name of the Manager. Keywords: Media, Community, Twitter, Planning, Monitoring, Optimisation Of Activation.